2004
DOI: 10.1210/jc.2004-0735
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Sex Hormones in Relation to Age, Sex, Lifestyle Factors, and Chronic Diseases in a General Population: The Tromsø Study

Abstract: The role played by endogenous hormones in many diseases makes it important to understand factors influencing their levels. This study examined the distribution of total and free estradiol, FSH, and dehydroepiandrosterone sulfate (DHEAS) by age and sex and associations of these hormones with body mass index (BMI), lifestyle factors, and chronic diseases. Plasma samples taken from 1555 men and 1952 women 25-84 yr of age in 1994-1995 Tromsø Study were analyzed in 2001. Total estradiol increased with age among men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
127
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(152 citation statements)
references
References 46 publications
18
127
4
3
Order By: Relevance
“…This inhibitory regulation by estrogens is consistent not only with the normal sex differences in COMT activity noted above, but with evidence that women with high estrogen states (eg on the combined oral contraceptive, or in the third trimester of pregnancy) have higher COMT activity than other women (Briggs and Briggs, 1973). In postmenopausal women, estrogen levels fall dramatically, to substantially below that of men of the same age (Bjornerem et al, 2004); it would be of interest to know if sexual dimorphisms in COMT activity (or its genetic associations) present in younger adults are lost or reversed in the elderly.…”
Section: Mechanisms Of Sexual Dimorphism In Comt Effects and Associatsupporting
confidence: 83%
See 1 more Smart Citation
“…This inhibitory regulation by estrogens is consistent not only with the normal sex differences in COMT activity noted above, but with evidence that women with high estrogen states (eg on the combined oral contraceptive, or in the third trimester of pregnancy) have higher COMT activity than other women (Briggs and Briggs, 1973). In postmenopausal women, estrogen levels fall dramatically, to substantially below that of men of the same age (Bjornerem et al, 2004); it would be of interest to know if sexual dimorphisms in COMT activity (or its genetic associations) present in younger adults are lost or reversed in the elderly.…”
Section: Mechanisms Of Sexual Dimorphism In Comt Effects and Associatsupporting
confidence: 83%
“…This fact also bears upon potential explanations for sexual dimorphism in COMT based upon epigenetic regulation (Kaminsky et al, 2006); in any event, there is no evidence for a sex difference in COMT methylation status (Abdolmaleky et al, 2006). Furthermore, the finding that COMT protein and activity levels rise considerably in men between the third and fifth decade of life (Tunbridge et al, 2007a), despite steady estradiol levels across this period (Bjornerem et al, 2004) emphasizes that estrogens are not the only factor responsible for regulating COMT in the brain.…”
Section: Mechanisms Of Sexual Dimorphism In Comt Effects and Associatmentioning
confidence: 99%
“…Plasma DHEA-S levels do not drop during the menopause transition, but decline with aging (1,2,20). A recent study has shown a positive correlation between DHEA-S levels and the duration of reactive hyperemia, another less specific marker of endothelial function compared to FMD, in young women (26±6 years old, n= 27) with polycystic ovary syndrome (21).…”
Section: Discussionmentioning
confidence: 92%
“…40 Women experience a rapid decline in sex hormones (estrogen) expressed with the cessation of menses. 41 It is possible that the reduction in estrogen levels to some degree counteracts the aging effect on tendon through causing women's tendon properties to deteriorate less (where increased compliance is considered a deterioration) with aging than men's.…”
Section: Discussionmentioning
confidence: 99%